Majority merging by adaptive counting. - Primiero, Giuseppe; Meheus, Joke (Synthese, 2008)
The present paper introduces a belief merging procedure by majority using the standard format of Adaptive Logics. The core structure of the logic ADM ( Adaptive Doxastic Merging by Counting) consists in the formulation of the conflicts arising from the belief bases of the agents involved in the procedure. A strategy is then defined both semantically and proof-theoretically which selects the consistent contents answering to a majority principle. The results obtained are proven to be equivalent to a standard majority operator for bases with partial support.